2006
DOI: 10.1111/j.1600-0714.2006.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased survivin expression in high‐grade oral squamous cell carcinoma: a study in Indian tobacco chewers

Abstract: Increased expression of anti-apoptotic survivin in high-grade tumors suggests that survivin is likely to contribute significantly to apoptosis resistance in response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
5
21
2
Order By: Relevance
“…These findings are consistent with the results for human oral carcinogenesis (Tanimotoa et al. 2005; Jane et al. 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with the results for human oral carcinogenesis (Tanimotoa et al. 2005; Jane et al. 2006).…”
Section: Discussionsupporting
confidence: 93%
“…1998), and the association of IAP family members, chiefly survivin, with human oral squamous‐cell carcinomas has also been studied (Tanimotoa et al. 2005; Jane et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Since the function of cytoplasmic survivin is to inhibit apoptosis, evasion from apoptosis may play a key role in the early event of oral carcinogenesis. 24,28,39 Interestingly, the high rate of cytoplasmic survivin expression (72% to 100%) in OSCC was consistently reported from various studies, [22][23][24]40 despite the differences in risk factors, geographic factors, criteria of evaluation of survivin expression, and antibody sources. It has been shown that apoptosis inhibited by survivin led to p53 mutant clones after ultraviolet B irradiation in a skin tumor model.…”
Section: Discussionmentioning
confidence: 74%
“…2 An important reason for poor prognosis of OSCC is the lack of molecular prognostic markers available to assess the aggressiveness of this tumour, probability of recurrence and disease progression. 3 Apoptosis has become one of the basic tools in cancer research and establishing cancer pathways. 4 Survivin is a protein that inhibits apoptosis and regulates cell division.…”
Section: Introductionmentioning
confidence: 99%